2022
DOI: 10.3389/fimmu.2022.882918
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 booster after heterologous prime-boost vaccination induces potent neutralizing antibodies and T cell reactivity against SARS-CoV-2 Omicron BA.1 in young adults

Abstract: In light of the decreasing immune protection against symptomatic SARS-CoV-2 infection after initial vaccinations and the now dominant immune-evasive Omicron variants, ‘booster’ vaccinations are regularly performed to restore immune responses. Many individuals have received a primary heterologous prime-boost vaccination with long intervals between vaccinations, but the resulting long-term immunity and the effects of a subsequent ‘booster’, particularly against Omicron BA.1, have not been defined. We followed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 83 publications
4
17
0
Order By: Relevance
“…Furthermore, in agreement with Beklitz et al, we showed decreased neutralizing capacities against Delta and Omicron in comparison to the SARS-CoV-2 WT (52). These observations are also in line with recent studies that demonstrated increased neutralizing antibody titers after first (prime-boost) (54) and second boost (prime-boost-boost) vaccination (39).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, in agreement with Beklitz et al, we showed decreased neutralizing capacities against Delta and Omicron in comparison to the SARS-CoV-2 WT (52). These observations are also in line with recent studies that demonstrated increased neutralizing antibody titers after first (prime-boost) (54) and second boost (prime-boost-boost) vaccination (39).…”
Section: Discussionsupporting
confidence: 93%
“…As a result of the SARS-CoV-2 pandemic, a considerable effort was made to investigate the safety and efficacy of newly generated vaccines. Recent studies have shown that heterologous and homologous prime-boost vaccine regimens result in adequate humoral and cellular immunity against SARS-CoV-2 ( 39 , 52 ), and prevent severe COVID-19 disease progression ( 53 ). Vaccines were initially developed against the ancestral SARS-CoV-2 Wuhan strain, and studies show that immunity against VOCs, especially Omicron, is equally achieved after the first ( 15 ) and second boost vaccination ( 47 ) of different vaccine regimens in terms of humoral immunity and rough T cell analysis ( 14 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three months after the third vaccine dose, antibody levels decrease at a similar rate as after the second vaccine dose, while spike-speci c CD4 + and CD8 + T cells persist and effectively cross-recognize spike protein peptide pools from Omicron BA.1 and BA.2 variants. Our results support the ndings of other T cell studies on mRNA-vaccinated individuals 3,13,14 indicating a durable cell-mediated immunity against SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 91%
“…Cellular immunity plays an important role in protecting individuals against severe cases of coronavirus disease 2019 (COVID-19), as reported in various studies, animal experiments [9,10], clinical studies [11,12,13,14,15,16,17,18,19,20], and general reviews [21,22,23]. Several studies showed booster vaccination induced stronger cellular immunity among relatively small number of participants or HCWs [24][25][26][27]. However, to this day, few studies have been conducted at the population level regarding cellular immunity after booster vaccination, and little is known about what proportion of population has achieved induced cellular immunity after booster vaccination and who is more likely to achieve it.…”
Section: Introductionmentioning
confidence: 99%